Pengembangan Multimedia Interaktif Berbasis Ispring Suite 8 sebagai Media Pembelajaran Pada Mata Pelajaran Praktikum Akuntansi Lembaga - Lailatul Fitriya Alfin; Agung Listiadi (Jurnal Dimensi Pendidikan dan Pembelajaran, 2021)
In a learning activity, learning media has a very important function for the learning process in the classroom. Through technology development, sophisticated ICTs make a major contribution to the world of education needed for learning media. One interactive multimedia application software that can be used is Ispring Suite 8, which can make the material more interesting and interactive based on flash. In the accounting expertise program and financial institutions additional subjects that must be learned by students, namely practicum of accounting institutions. Therefore it is necessary to develop multimedia for the subjects of institutional accounting practicum. This research belongs to the development research with the ADDIE development model. The feasibility of this interactive multimedia can be known by looking at the results of the validation of the experts while to find out the opinions of students related to the media developed, limited trials were conducted on 20 students of class XI Accounting and financial institutions. The results of the validation of the material experts and media experts showed an average percentage of 90.11% classified as